How Elite Athletes with a Spinal Cord Injury Sweat during Exercise-An Exploratory Study - Anneke Hertig-Godeschalk; Claudio Perret (MDPI AG, 2024)
Background: Sweat and thermal responses in individuals with spinal cord injury (SCI) are impaired depending on lesion characteristics. This is particularly problematic for athletes and may ultimately lead to reduced performance. This exploratory study investigated the feasibility of field-usable methods to objectively collect data relevant to sweat response in elite athletes with SCI. Differences in sweat response were also evaluated for different athlete characteristics. Methods: Measurements were performed during exercise and included core temperature (Tc), heart rate, urine specific gravity, fluid intake, sweat rate, and sweat electrolyte concentration. Differences for sex, lesion level (tetraplegia versus paraplegia), motor impairment (complete versus incomplete), and sport type (endurance versus team/skill) were evaluated. Results: Fifteen athletes (median (Q1-Q3) age, 30 (28-36) years; three females; 11 with complete lesions) were included. Endurance athletes were measured during indoor performance tests (n = 10), whereas team/skill athletes were measured during training sessions (n = 5). In the mixed exercise intensities, the average Tc was 37.7 (37.3-37.8) °C and the average heart rate was 126 (100-146) bpm. Dehydration, defined as a urine specific gravity > 1.020 ng/mL, was prevalent in six athletes before exercise and in five athletes after exercise. The sweat rate was lower in athletes with tetraplegia (p = 0.02) and in team/skill athletes (p = 0.008). Conclusions: Collecting sweat and thermal response data from athletes with SCI in the field is feasible. Given the suboptimal hydration status of many athletes, raising awareness of the importance of hydration seems valuable.